Incidence and serological detection of viruses infecting tomato and cultural control practices in Kwara State of Nigeria - Aliyu, T. H.; Popoola, J.; Arogundade, O.; Sanni, S. A.; Adeboye, R. S.; Salman, A. A. (Journal of the Bangladesh Agricultural University, 2020)
Tomato (Lycopersicon esculentum Mill) is one of the major fruit vegetables in Nigeria and viruses cause significant losses in both field and greenhouse tomato production systems. The study was conducted in Kwara State of Nigeria to determine the incidence of virus diseases on tomato and detect the suspected viruses with serological assay. A field experiment was then initiated to evaluate varietal inherency, plant spacing and staking as cultural control practices on viral incidence. A virus disease survey of 35 major tomato producing farmlands in the study area was done to determine incidence of virus infection. Twenty (20) leafy shoot samples from each farmland were then randomly collected for serological study. The serological assay of samples was by ACP-ELISA; each tested for 3 viruses known to commonly infect tomato in Africa namely: Pepper veinal mottle virus (PVMV), Tomato spotted wilt virus (TSWV) and Tomato yellow leaf curl virus (TYLCV). The field experiment involved sowing 2 tomato varieties at varying plant spacing (30cm x 60cm and 60cm x 75cm) and either staked or non-staked. The experimental design was a factorial fitted into Randomized Complete Block Design (RCBD) of 8 treatments combinations with 4 replications. The result of the virus survey indicated incidence of 4.8% to 38.9% with an average value of 20.3%. The ACP-ELISA revealed major occurrence in the study area of the 3 viruses with PVMV being the most prevalent on the samples. The field experiment showed that Roma VF tomato variety, staked and at plant spacing of 30 x 75cm was the most effective in reducing the incidence of virus disease (2.2% - 6.1%), had the tallest plants (8.6cm–18.0cm), produced the highest average number of leaves per plant (13.7 – 20.5) and tomato fruit weight (406.7g). The study concludes that virus infection may become a serious threat to tomato production in the study area and therefore recommends a combination of resistant variety (Roma VF), plant spacing (30 x 75cm) and staking for effective virus management to ensure higher yield. J Bangladesh Agril Univ 18(2): 266–271, 2020 https://doi.org/10.5455/JBAU.90126